srpski - Ojediran, K Taiwo; Adewale (Journal of Agricultural Sciences (Belgrade), 2021)
Three hundred (300) 21d old (Arbor-acre) broiler chicks apportioned to five (5) dietary groups of sixty (60) birds each, further replicated six (6) times were fed toasted pigeon pea seed meal to assess the performance, flock uniformity, organ weights, carcass yield and hepatic histology at the finisher phase. A maize-full fat soybean meal diet served as the control diet (I). The toasted Pigeon pea seed meal was incorporated to replace full fat soybean meal at 12.5%, 25.0%, 37.5% and 50.0% in diets II, III, IV and V respectively. Toasting improved the protein content, ether extract, fibre content, metabolizable energy and reduced the anti-nutrients except oxalate. The final weight, total weight change, average weight gain and feed conversion quotent were significant influenced (P<0.05) unlike the average feed intake, mortality and flock uniformity (P>0.05). The eviscerated weight, breast yield, thigh yield, kidney and abdominal fat were also influenced (P<0.05). There were varying levels of hepatic degeneration which increased in intensity as the level of inclusion increased. It ranges from mild sinusoidal congestion, cellular infiltration and necrosis of the cell in the liver. Up to 37.5% toasted pigeon pea seed meal replacement for soybean meal supported optimum growth, breast and thigh yield, and mild to moderate hepatic distruptions